STUDY OF THE INFLUENCE LEVEL CURRENT OF THE SHORT CIRCUIT ON RELIABILITY OF THE BREAKERS - Erhan F.; Popescu V.; Lopushor I.; Mocanu I. (Problems of the Regional Energetics)
In the article the analysis of the influence level current of the short circuit of the electrical equipment. It is designed the mathematical model allowing the modeling prototype reliability of the operation electrical equipment installed in nodes of the systems.